An unusual complication of foley catheterization in a child: Urethral foreign body - Yeliz Kart; Emine Bilaloglu; Levent Duman (Wolters Kluwer Medknow Publications, 2021)
Iatrogenic urethral foreign bodies are rare conditions in clinical practice, and the relevant data are limited to adult cases in the literature. In this paper, we presented a pediatric case in which a fragment of Foley catheter balloon remained in the posterior urethra.